2023
DOI: 10.1182/blood.2022018193
|View full text |Cite
|
Sign up to set email alerts
|

A RUNX1-FPDMM rhesus macaque model reproduces the human phenotype and predicts challenges to curative gene therapies

Abstract: Germline loss-of-function heterozygous mutations in the RUNX1 gene cause Familial Platelet Disorder with associated Myeloid Malignancies (FPDMM), characterized by thrombocytopenia and a life-long risk of hematological malignancies. Although gene therapies are being considered as promising therapeutic options, current preclinical models do not recapitulate the human phenotype and are unable to elucidate the relative fitness of mutation-corrected and RUNX1-heterozygous mutant HSPCs in vivo long-term. We generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The functional analysis in transplantation assays demonstrated that Runx1 R188Q/+ HSPCs have higher LT-RC than WT counterparts. Accordingly, a recent study reported the engraftment of RUNX1 -edited HSPCs in rhesus macaques, 49 underscoring the role of Runx1 mutations in preleukemic expansion and highlighting the concerns on the use of potential gene-editing therapies in premalignant FPDHM HSCs. In addition, this analysis reveals that Runx1 R188Q/+ HSPCs have selective expansion in both genetic backgrounds, albeit the differences seen in HSPC compartment, indicating that nonhematopoietic cells have negligible impact on the long-term expansion of Runx1-mutant HSPCs.…”
Section: Discussionmentioning
confidence: 96%
“…The functional analysis in transplantation assays demonstrated that Runx1 R188Q/+ HSPCs have higher LT-RC than WT counterparts. Accordingly, a recent study reported the engraftment of RUNX1 -edited HSPCs in rhesus macaques, 49 underscoring the role of Runx1 mutations in preleukemic expansion and highlighting the concerns on the use of potential gene-editing therapies in premalignant FPDHM HSCs. In addition, this analysis reveals that Runx1 R188Q/+ HSPCs have selective expansion in both genetic backgrounds, albeit the differences seen in HSPC compartment, indicating that nonhematopoietic cells have negligible impact on the long-term expansion of Runx1-mutant HSPCs.…”
Section: Discussionmentioning
confidence: 96%
“…Notwithstanding, the integration of the transgene was stable for at least 45 Tracking studies of corrected HSPCs in Wiscott-Aldrich syndrome or βhemoglobinopathy patients have estimated that as few as 98 corrected HSPCs per 10 6 infused CD34 + cells are able to engraft the bone marrow for long term-production of granulocytes 48 . Given that our experiments were designed using relatively small cell numbers (2.5x10 5 to 1x10 6 CD34 + HSPCs per single nucleofection targeting one candidate GSH site), the results suggest that the scaling-up to clinical preparation numbers (usually >5X10 6 electroporated cells) would increase the bioavailability of therapeutic cells 44,51 . Alternatively, if low cell numbers are involved, the rAAV6 vectors reportedly substantially increase editing efficiencies.…”
Section: Gsh Targeted Integration In Human Cd34 + Hspcsmentioning
confidence: 99%
“…A recent study on gene therapy-patients suffering Wiscott-Aldrich syndrome or βhemoglobinopathies estimated that as few as 98 corrected HSPCs per 10 6 infused CD34+ cells were able to engraft the bone marrow for long term-production of granulocytes according to the tracking of unique vector insertion sites (IS) 47 . Given that our experiments were designed on a small scale of cell numbers (2.5x10 5 to 1x10 6 CD34+ HSPCs per single nucleofection targeting one candidate GSH site), the results suggest that the scaling-up to clinical preparation numbers (usually >5X10 6 electroporated cells) would increase the bioavailability of therapeutic cells 43,49 .…”
Section: Gsh Targeted Integration In Human Cd34+ Hspcsmentioning
confidence: 99%